(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
this methodical recommendation is to organize the science of physical education in general education schools and to give a recommendation on the role of rhythmic gymnastics and its use in lessons in educating students to be healthy, well-rounded, fit and attractive.